Preparation and Mechanical Characterizations of Water Hyacinth Fiber Based Thermoset Epoxy Composite - Macaulay Mfon Owen; Emmanuel Okechukwu Achukwu; Hazizan Md Akil (Journal of Natural Fibers, 2022)
Composites of water hyacinth fiber thermoset epoxy (WHE) composites were developed and characterized. Water hyacinth (WH) fibers were treated in an optimized 6% concentration of sodium hydroxide (NaOH) solution for an hour before composite fabrication by mixing with an epoxy resin (E) matrix. Fourier Transform Infrared (FTIR) and Field Emission Scanning Electron Microscopy (FE-SEM) analyses were conducted on both the treated water hyacinth (TWH) and untreated water hyacinth (WH) fibers, and the constituent composites. The mechanical properties (such as tensile, flexural, and impact) of the WHE composites were tested. The results obtained showed that treated water hyacinth epoxy composites (TWHE) provided better mechanical properties with remarkable improvement of up to 13%, 17%, and 7% for tensile, flexural, and impact strength, respectively, in comparison with untreated water hyacinth epoxy composites (WHE). FESEM results revealed strong fiber/matrix interfacial bonding between the treated fibers and epoxy matrix while the untreated WHE composites showed evidence of poor compatibility between the untreated WH fibers and the epoxy matrix, thus decreasing the mechanical properties of the composites. The results have demonstrated that water hyacinth fibers have the potential as an alternative material to replace synthetic fibers in composite applications.